One-Step Assembly of a PRRSV Infectious cDNA Clone and a Convenient CRISPR/Cas9-Based Gene-Editing Technology for Manipulation of PRRSV Genome - Hejin Zhang; Kaiqi Duan; Yingbin Du; Shaobo Xiao; Liurong Fang; Yanrong Zhou (Viruses, 2023)
Porcine reproductive and respiratory syndrome (PRRS) has been a persistent challenge for the swine industry for over three decades due to the lack of effective treatments and vaccines. Reverse genetics systems have been extensively employed to build rapid drug screening platforms and develop genetically engineered vaccines. Herein, we rescued recombinant PRRS virus (rPRRSV) WUH3 using an infectious cDNA clone of PRRSV WUH3 acquired through a BstXI-based one-step-assembly approach. The rPRRSV WUH3 and its parental PRRSV WUH3 share similar plaque sizes and multiple-step growth curves. Previously, gene-editing of viral genomes depends on appropriate restrictive endonucleases, which are arduous to select in some specific viral genes. Thus, we developed a restrictive endonucleases-free method based on CRISPR/Cas9 to edit the PRRSV genome. Using this method, we successfully inserted the exogenous gene (EGFP gene as an example) into the interval between ORF1b and ORF2a of the PRRSV genome to generate rPRRSV WUH3-EGFP, or precisely mutated the lysine (K) at position 150 of PRRSV nsp1α to glutamine (Q) to acquire rPRRSV WUH3 nsp1α-K150Q. Taken together, our study provides a rapid and convenient method for the development of genetically engineered vaccines against PRRSV and the study on the functions of PRRSV genes.